Mahar Terhutang dalam Perkawinan Islam: Tinjauan Yuridis Berdasarkan Kompilasi Hukum Islam - Muhammad I Iqbal; Khairudin Nor; Ahmad Zaky Kurniawan; Maulagina Azkiya Mazidah (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Mahr (dowry) is the right of the wife that must be fulfilled by the husband in an Islamic marriage. In practice, there are many cases where the mahr has not been handed over at the time of the marriage contract and subsequently becomes a legally binding debt owed by the husband. This study aims to juridically examine the legal standing of deferred mahr based on the provisions of the Islamic Law Compilation (KHI) of Indonesia, to analyze the views of Islamic jurists from various schools of law on the matter, and to explore its legal implications in cases of divorce or the husband’s death. This study employs a normative juridical method with statutory and conceptual approaches, supported by primary legal sources in the form of the KHI and secondary sources consisting of classical fiqh literature and relevant scholarly works. The findings indicate that Article 33 paragraph (2) of the KHI permits the deferral of mahr delivery upon the wife’s consent, and that the undelivered mahr becomes a mandatory debt for the husband to repay. Article 34 paragraph (2) affirms that the existence of a deferred mahr does not diminish the validity of the marriage. The four major schools of Islamic law generally agree on the permissibility of deferring mahr, though they differ regarding the conditions and time limits involved. The mahr debt remains binding even after the marriage has ended, whether through divorce or the husband’s death, and may be taken from the estate if the husband passes away. This study concludes that the regulation of deferred mahr in the KHI reflects a balance between legal flexibility and the protection of the wife’s rights, while emphasizing the need to improve public legal awareness so that this obligation is not overlooked.